The Application Of Tort Law In Addressing Issues In Halal Pharmaceutical Products: Safeguarding Consumers Rights - Nasihah Naimat; Mimi Sofiah Ahmad Mustafa; Nasreen Miza Hilmy Nasrijal; Ida Rahayu Mahat (USIM PRESS, 2024)
Indexed by Scopus